2021
DOI: 10.53365/efood.k/147240
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of flavonoids isolated from Agrocybe aegirita on dextran sodium sulfate‐induced colitis

Abstract: Mushroom derived phytochemical has become the promising agent to treat inflammatory bowel disease (IBD). Here, we investigated the effect of flavonoids from <i>Agrocybe aegirita</i> (AAF) on dextran sodium sulfate-induced colitis. Our results showed that flavonoids from <i>Agrocybe aegirita</i> had a certain effect on physical signs in mice (improving the weight loss of mice, reducing reducing the DAI index and the spleen index of mice). AAF could also significantly reduce the shortenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The experimental factors and levels are shown in Table A.1 . The determination of total flavonoids was carried out according to existing methods ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental factors and levels are shown in Table A.1 . The determination of total flavonoids was carried out according to existing methods ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although more and more reports have been published in recent years, research on A. cylindracea in China was still mainly focused on cultivation (Benshou et al, 2018), bioactive substances (Kanno et al, 2021; Li et al, 2021; Zhang et al, 2021), and comparison with other edible mushrooms (Jacinto‐Azevedo et al, 2021). There are no reports of nutritional features of A. cylindracea associated with its strains and geographical features.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are abundant biomacromolecules in nature and are widely found in plants, animals, and microorganisms (fungi and bacteria). In recent years, numerous studies had revealed that polysaccharides from natural sources had various bioactive functions, such as immunoregulation (Sun et al, 2021), regulation of gut microbiota (H. Lin, Zhang, et al, 2021), antitumor (Zhao et al, 2020), anti‐inflammatory (J. Zhang et al, 2021), blood sugar and lipid regulation (Y. Zhang et al, 2021), and so on. Its extraction and purification are the first and also one of the most critical parts of complex carbohydrate study.…”
Section: Introductionmentioning
confidence: 99%